2020
DOI: 10.1038/s41467-020-14638-w
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous topoisomerase II-mediated DNA breaks drive thymic cancer predisposition linked to ATM deficiency

Abstract: The ATM kinase is a master regulator of the DNA damage response to double-strand breaks (DSBs) and a well-established tumour suppressor whose loss is the cause of the neurodegenerative and cancer-prone syndrome Ataxia-Telangiectasia (A-T). AT patients and Atm −/− mouse models are particularly predisposed to develop lymphoid cancers derived from deficient repair of RAG-induced DSBs during V(D)J recombination. Here, we unexpectedly find that specifically disturbing the repair of DSBs produced by DNA topoisomeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
2
10
0
1
Order By: Relevance
“…The DNA topoisomerases (topos) are critical enzymes involved in modulation of breaking and rejoining of DNA strand (Liu et al, 2020). There are two characteristic types of topos including DNA topoisomerase 1 (topo1) and DNA topoisomerase 2 (topo2) that have been shown to regulate chromosomal segregation and DNA replication, recombination and repair (Alvarez‐Quilon et al, 2020; Singh, Luxami, & Paul, 2020). Consequently, much attention has been directed towards targeting topos in cancer therapy to suppress growth and proliferation of cancer cells (Shu et al, 2020; Watanabe et al, 2020).…”
Section: Cryptotanshinone and Cancermentioning
confidence: 99%
“…The DNA topoisomerases (topos) are critical enzymes involved in modulation of breaking and rejoining of DNA strand (Liu et al, 2020). There are two characteristic types of topos including DNA topoisomerase 1 (topo1) and DNA topoisomerase 2 (topo2) that have been shown to regulate chromosomal segregation and DNA replication, recombination and repair (Alvarez‐Quilon et al, 2020; Singh, Luxami, & Paul, 2020). Consequently, much attention has been directed towards targeting topos in cancer therapy to suppress growth and proliferation of cancer cells (Shu et al, 2020; Watanabe et al, 2020).…”
Section: Cryptotanshinone and Cancermentioning
confidence: 99%
“…To further test the predictive power of our approach, we generated genome wide predictions in mouse thymocytes and used TOP2B ChIP-seq data performed in our laboratory [ 60 ] to validate them. In order to test the specificity of our model, we evaluated the ChIP-seq signal generated by two different antibodies (Novus and Santa Cruz).…”
Section: Resultsmentioning
confidence: 99%
“…Upon etoposide treatment, abortive TOP2 activity results in DSBs at CTCF-RAD21 sites, as measured by the END-seq method [ 12 , 17 ]. Since TOP2-induced DSBs have important implications for cancer-linked translocations [ 12 , 17 , 18 , 60 , 61 ], we decided to test the capacity of our model to predict these breaks. Given that many of the datasets provided by Canela et al (2017) correspond to MEFs, we focused our analysis on this cell line and processed an END-seq sample treated with etoposide in addition to the already analyzed TOP2B ChIP-seq dataset (see S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…experimental TOP2B tracks in both organisms, showing that our model can be used to 48 generate virtual TOP2B signals in potentially any mammalian cell type and condition 49 for which sequencing data of CTCF, RAD21 and DNase I hypersensitivity are available. 50 Materials and methods 51 Processing publicly available data 52 The experimental data used in this study is summarized in S1 Table. When available, 53 we batch-downloaded mm9 and hg19 BAM files from ENCODE.…”
mentioning
confidence: 97%
“…The achieved predictions showed that the cross-cell type applications of the classifiers 398 did not decrease their performances, which acquired accurate predictions independently 399 of the training cell type ( Fig 4C; S4 Fig; Table 4). For example, when we applied NB 400 To further test the above observations, we used genome wide ChIP-seq TOP2B 405 binding in mouse thymocytes obtained in our laboratory [49] and assessed model 406 prediction accuracies on them. This time we generated models using a combination of 407 data from mouse liver, MEFs and activated B cells, which allowed us to better capture 408 the cell type specificities of TOP2B binding in a single classifier.…”
mentioning
confidence: 99%